Abdominal Adiposity, General Obesity, and Subclinical Systolic Dysfunction in the Elderly. A Population-Based Cohort Study - Russo, Cesare (Eur J Heart Fail, 2016)
AIMS: General obesity, measured by the body mass index (BMI), and abdominal adiposity, measured as waist circumference (WC) and waist-to-hip ratio (WHR), are associated with heart failure and cardiovascular events. However, the relationship of general and abdominal obesity with subclinical left ventricular (LV) dysfunction is unknown. We assessed the association of general and abdominal obesity with subclinical LV systolic dysfunction in a population-based elderly cohort. METHODS AND RESULTS: Participants from the Cardiovascular Abnormalities and Brain lesions study underwent measurement of BMI, WC, and WHR. LV systolic function was assessed by two-dimensional echocardiographic LV ejection fraction (LVEF) and speckle-tracking global longitudinal strain (GLS). The study population included 729 participants (mean age 71±9 years, 60% women). In multivariate analysis, higher BMI (but not WC and WHR) was associated with higher LVEF (β=0.11, p=0.003). Higher WC (β=0.08, p=0.038) and higher WHR (β=0.15, p<0.001) were associated with lower GLS, whereas BMI was not (p=0.720). Compared with normal WHR, high WHR was associated with lower GLS in all BMI categories (normal, overweight, and obese), and was associated with subclinical LV dysfunction by GLS both in participants without (adjusted OR=2.0, 95% CI=1.1-3.6, p=0.020) and with general obesity (adjusted OR=5.4, 95% CI=1.1-25.9, p=0.034). WHR was incremental to BMI and risk factors in predicting LV dysfunction. CONCLUSION: Abdominal adiposity was independently associated with subclinical LV systolic dysfunction by GLS in all BMI categories. BMI was not associated with LV dysfunction. Increased abdominal adiposity may be a risk factor for LV dysfunction regardless of the presence of general obesity.